2020
DOI: 10.3390/microorganisms8040465
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine Residues in Helicobacter pylori Adhesin HopQ Are Required for CEACAM–HopQ Interaction and Subsequent CagA Translocation

Abstract: Attachment to the host gastric mucosa is a key step in Helicobacter pylori infection. Recently, a novel adhesin, HopQ, was shown to bind distinct host CEACAM proteins—an interaction that was found to be essential for the translocation of CagA, a key virulence factor of H. pylori. The HopQ–CEACAM1 co-crystal structure revealed a binding mode dependent on loops in HopQ that are clasped by disulfide bonds. In this study, we investigated the importance of these cysteine residues for CEACAM1 engagement by H. pylori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…That cysteine residues and disulfide bond formation are likely involved in the type IV secretion process, is indicated by the deficiency of an H. pylori deletion mutant in the disulfide bond oxidoreductase gene hp0231 for CagA translocation (Zhong et al, 2016). Furthermore, the outer membrane protein HopQ, which plays an important role in the translocation process, requires disulfide bonds for its interaction with CEACAM receptors (Hamway et al, 2020). However, a hopQ mutant of strain P12 is still able to translocate reduced levels of CagA into AGS cells (Zhao et al, 2018), and even this reduced translocation could be inhibited by adding cisplatin (data not shown), arguing against a major role of HopQ in the type IV secretion inhibition observed here.…”
Section: Discussionmentioning
confidence: 99%
“…That cysteine residues and disulfide bond formation are likely involved in the type IV secretion process, is indicated by the deficiency of an H. pylori deletion mutant in the disulfide bond oxidoreductase gene hp0231 for CagA translocation (Zhong et al, 2016). Furthermore, the outer membrane protein HopQ, which plays an important role in the translocation process, requires disulfide bonds for its interaction with CEACAM receptors (Hamway et al, 2020). However, a hopQ mutant of strain P12 is still able to translocate reduced levels of CagA into AGS cells (Zhao et al, 2018), and even this reduced translocation could be inhibited by adding cisplatin (data not shown), arguing against a major role of HopQ in the type IV secretion inhibition observed here.…”
Section: Discussionmentioning
confidence: 99%
“…The synergy between HopQ and CagA co-expression is recognized as a facilitated activity of several pro-inflammatory pathways, including NF-κB or those associated with mitogen-activated protein kinases (MAP kinases) via T4SS since HopQ significantly facilitates T4SS activity [ 273 ]. The interaction with T4SS and CagA translocation and/or phosphorylation induced by HopQ is stimulated by HopQ binding to host the carcinoembryonic antigen-related cell adhesion molecules (CEACAM) proteins (primarily CEACAM1, CEACAM3, CEACAM5, and CEACAM6) expressed on gastric epithelial cells promoting NF-κB activation [ 274 , 275 , 276 , 277 , 278 , 279 , 280 ]. This, as a consequence, might induce the development of gastric ulcers and facilitate gastric carcinogenesis.…”
Section: Helicobacter Pylori Outer Membrane Prmentioning
confidence: 99%
“…Binding of H. pylori to CEACAM receptors is mediated by the adhesin HopQ. This interaction is not only essential for binding of H. pylori to the gastric epithelium but also for cag pathogenicity island (cagPAI)-dependent CagA translocation and induction of IL8 secretion by gastric epithelial cells, thereby modulating the host immune response [ 19 , 37 , 39 ]. In this immune response, the activation of the non-canonical NF-κB pathway plays a crucial role, as we previously observed that this signalling pathway is important for the recruitment of immune cells to the stomach upon H. pylori infection [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…H. pylori was grown on WC Dent agar plates for 48 h, the optical density was measured and adjusted to 2 × 10 8 bacteria in 1 mL media, and the bacteria was stained for 30 min with 10 µM carboxyfluorescein succinimidyl ester (CFSE, eBioscience, San Diego, CA, USA) [ 39 ]. The labeled bacteria were washed twice and added at an MOI of 10 to 1 × 10 5 cells, which were previously seeded in a 96-well V bottom plate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation